Adaptivna protonska radioterapija - Klopčič, Sara (Matrika, 2021)
The advantage of proton radiotherapy over photon radiotherapy is in more localized dose distribution, which accurs in the area of Bragg peak. The energy loss rate of protons inside a body is described by Bethe-Bloch equation. Before the beginning of the treatment, it is necessary to make a treatment plan with the help of analytical models of physical processes and use of computer simulations such as Monte Carlo simulations. When treating with adaptive radiotherapy, changes in the tumor area are observed before every irradiation, which can be done every few days or weeks, depending on the treatment plan. To achieve better results, real-time imaging methods are being developed. One of the possibilities of monitoring the dose distribution in the body is with detection of emitted gamma rays and with real-time magnetic resonance imaging.
Keywords: irradiation; medical physics; medicinska fizika; obsevanje; oncology; onkologija; proton radiotherapy; protonska radioterapija